An ethnography of construction and characteristics of curriculum for inheritance of intangible cultural heritage martial arts in universities - Cheng, Yuanlong; Guo, Nana (Frontiers in Sports and Active Living, 2024)
Background: Inheriting excellent traditional Chinese culture is a prerequisite for ensuring the continuity of the cultural genes of the Chinese nation. However, with the historical mission of shaping the national character of the descendants of the Chinese nation, intangible cultural heritage martial arts face the problem of unclear curriculum content construction mechanism in university inheritance, and make it difficult for intangible cultural heritage martial arts to shoulder the responsibility of cultural inheritance in the era.Method:Educational ethnography as a research method is conducive to in-depth exploration of the mechanism of curriculum content construction in the inheritance of intangible cultural heritage martial arts in universities.Results:Research suggests that the construction of curriculum content for the inheritance of intangible cultural heritage martial arts in universities relies on the form of cooperation between universities and inheritors, and form three models of curriculum content construction: off campus, on campus, and on campus cooperation. The construction of curriculum content for off campus inheritors belongs to the "attachment style" model, which is based on the actual needs of the inheritors and the selection of boxing types; The construction of curriculum content for inheritors on campus belongs to the "reshaping" model, which is the inheritor's "simplification and reorganization" based on traditional routines and subjective and objective conditions of inheritance; The construction of course content in school local cooperation belongs to the "integrated" model, which is the re integration of course content by universities based on their own development characteristics and the characteristics of various martial arts.Conclusion:In inheritance of intangible cultural heritage martial arts in universities, emphasis is placed on local knowledge, core skills, cultural traditions, and other characteristics, highlighting the excellence of its cultural inheritance. In the future, the focus of intangible cultural heritage martial arts university inheritance is to cultivate innovative talents who are familiar with both traditional and modern martial arts.